On the 60th anniversary of the Institute of Forest and Forest Park Management of the Primorsky State Agricultural Academy - G. V. Gukov; B. S. Petropavlovskiy (Сибирский лесной журнал, 2019)
«The forest is the national wealth and heritage of our country. Russia is a great forest power» – is stated in many government decrees, as well as in textbooks, manuals and other publications. In order to use forest resources in the Russian Far East wisely, in 1958, the leaders of the former Soviet Union established the Faculty of Forestry in the city of Ussuriysk, Primorsky Krai. In 1963, the first year groups were formed, with 50 students recruited. Forty nine of them got the diplomas of forestry engineers. All the graduates were qualified as specialists in forestry and forest industries, many of them became industry managers, six graduates were awarded the degrees of PhDs and Doctors of Science. Over the past fifty years 55 groups of students were awarded the diplomas. They were qualified as forest engineers, later as Bachelors and Masters of Forestry. Forest industry of the Russian Far East has acquired several thousand specialists with higher forest education. The past 60 years have been associated with radical reforms in the field of social relations (the collapse of the Soviet Union, the transition to market economy), as well as in forest management. The Forest charter adopted by the State Duma in December of 2006 incorporated many ideas of forest science developed in our country and abroad. On the other hand, at present higher professional education is challenged by closing universities, introducing two-tier higher education, closing dissertation councils, increasing requirements to the applicants for doctoral degrees, and so on. We believe that Russia as a great forest power should have its own Ministry of Forestry which should a supplement to other Ministries.